2018
DOI: 10.1039/c8cc01931b
|View full text |Cite
|
Sign up to set email alerts
|

Coordination chemistry within a protein host: regulation of the secondary coordination sphere

Abstract: Secondary coordination spheres of metal complexes are instrumental in controlling properties that are linked to function. To study these effects in aqueous solutions artificial Cu proteins have been developed using biotin–streptavidin (Sav) technology and their binding of external azide ions investigated. Parallel binding studies were done in crystallo on single crystals of the artificial Cu proteins. Spectroscopic changes in solution are consistent with azide binding to the Cu centers. Structural studies corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…This tutorial considers molecular coordination compounds only, though artificial metalloproteins have also been used to manipulate SCS environments. [1][2][3] 2. Hydrogen bond acceptors…”
Section: Introductionmentioning
confidence: 99%
“…This tutorial considers molecular coordination compounds only, though artificial metalloproteins have also been used to manipulate SCS environments. [1][2][3] 2. Hydrogen bond acceptors…”
Section: Introductionmentioning
confidence: 99%
“…Further work by Hodges and co-workers showed that the stabilising effect of La 3+ addition on their coiled coils was highly dependent on the position of the Gln to Glu substitutions. 112 Three peptides were made, (E 2 (15,20), E 2 (13,22) and E 2 (20,22), Table 1), with varying distances between the two repulsive Glu e and g residues. Addition of LaCl 3 had a greater stabilising effect on E 2 (15,20) coiled coil formation than for E 2 (13,22), reflecting the reduction in the magnitude of Glu-Glu repulsion as the distance between them increases.…”
Section: Lanthanides At the Interhelical Interfacementioning
confidence: 99%
“…112 Three peptides were made, (E 2 (15,20), E 2 (13,22) and E 2 (20,22), Table 1), with varying distances between the two repulsive Glu e and g residues. Addition of LaCl 3 had a greater stabilising effect on E 2 (15,20) coiled coil formation than for E 2 (13,22), reflecting the reduction in the magnitude of Glu-Glu repulsion as the distance between them increases. Whilst, of the three peptides, the Glu residues are physically closest in the E 2 (20,22) Hydrophobic residues are black and salt bridge interactions between g and e residues are shown (red).…”
Section: Lanthanides At the Interhelical Interfacementioning
confidence: 99%
See 2 more Smart Citations